English content knowledge coverage and vertical alignment: Across levels document analysis of curriculum frameworks - Sri Wahyuni; Dadang Sudana; Bachrudin Mustafa; Ika Lestari Damayanti (Universitas Papua, 2026)
Coherent sequencing of content knowledge across the successive levels of teacher education shapes how prospective English teachers build subject-matter expertise, while vertical alignment across these levels remains underexamined in Indonesia. This study examines how content knowledge is sequenced and vertically integrated across three institutional levels of the Indonesian English teacher education continuum: senior high school, undergraduate teacher education, and the professional teacher education program. The study used qualitative document analysis within an interpretive paradigm. Nineteen officially mandated curriculum documents were analyzed with a Content Knowledge Coding Framework derived from Shulman’s account of teacher knowledge, comprising five domains and twenty subdomains. Coding proceeded through a level analysis and cross-level comparison, classifying each subdomain as aligned, partially aligned, or absent. The analysis shows horizontal consistency alongside vertical fragmentation. The findings show that the four language skills, grammar, vocabulary, and learning outcomes, are consistently represented across all educational levels. However, phonology, discourse, assessment literacy, pedagogical content knowledge, and technological knowledge are inconsistently represented or absent. The lack of formal articulation among the three curriculum frameworks contributes to only moderate vertical coherence, with a score of 68 of 120. These results suggest that persistent instructional weaknesses stem primarily from curriculum design, highlighting the need for cross-level curriculum reform.